Does Public Service Motivation Matter to Employees’ Performance and Organizational Commitment in Sub-district Offices? - Arif Budy Pratama; Aidah Nurhidayah (Magister Ilmu Administrasi Publik, 2019)
Many studies on Public Service Motivation (PSM) were conducted extensively in the developed countries, including US and Western Europe. In addition, some research on PSM has been conducted in Eastern Asia, all which affirm the positive role that plays in in shaping the public sector. That said, studies on PSM in developing countries, including Indonesia is still limited. This is despite the fact that previous research associate PSM with improving public sector performance. The objective of this study is to investigate the relationship between public service motivation, organizational commitment, and individual performance in Magelang Municipality, which is one of the high performing local govern,ents in Indonesia. The data was drawn from 70 government employees in 3 Magelang Municipality sub-district Offices. Meanhwile, to to test the research hypothesises. Structural Equation Modelling (SEM) was used. Resulst of the study validated the previous research findings that indicate positive influence of PSM on organizational commitment and individual performance. The result of this study has a practical implication for human resource development policy in Indonesian public sector. To that end, Public managers should take into account PSM in their managerial practices as it influences employee performance.